Photoirradiation Caused Controllable Wettability Switching of Sputtered Highly Aligned c-Axis-Oriented Zinc Oxide Columnar Films - P. W. Chi; C. W. Su; B. H. Jhuo; D. H. Wei (International Journal of Photoenergy)
This study presents the microstructure morphology and UV photoirradiation coupling effects of the c-axis-oriented zinc oxide (ZnO) columnar films. Highly aligned c-axis-oriented films have been deposited onto glass substrates at room temperature by radio-frequency (RF) magnetron sputtering without introducing any oxygen source under different sputtering powers ranging from 50 to 150 W. Self-assembled ZnO columnar structures that were successfully obtained belong to wurtzite structure, and the corresponding columnar structures and crystalline orientation were confirmed by the FE-SEM and XRD, respectively. All the ZnO columnar films exhibit good transparency with a visible light averaged transmittance over 82%. According to water contact angle (CA) measurement, ZnO columnar films exhibit hydrophobic behavior. After exposing to photoirradiation under ultraviolet (UV) environment, all the ZnO samples showed remarkable transition from hydrophobic to superhydrophilic surfaces and could return to their original hydrophobicity after being placed in the dark. It is demonstrated that the controllable wettability of ZnO columnar films under changing between the UV photoirradiation and dark storage is due to the surface charges accumulation and discharging processes. As a result, this study could provide important applications for many fields such as ZnO-based hybrid sensors/solar cells functional devices with photoirradiation disinfection surfaces accompanied with reversible wettability switches.